Analisis Semantik Puisi Hatiku Selembar Daun oleh Sapardi Djoko Damono - Elma Natalia Purba; Fitri Handayani Chaniago; Shafira Rahma Dina Sinaga; Asima Simbolon; Yuliana Sari (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
Poetry is a literary work full of meaning and symbolism. One poem that is interesting to analyze semantically is